Incidental pT2‐T3 gallbladder cancer after a cholecystectomy: outcome of staging at 3 months prior to a radical resection. Issue 8 (7th January 2013) - Ausania, Fabio; Tsirlis, Theodoris; White, Steven A.; French, Jeremy J.; Jaques, Bryon C.; Charnley, Richard M.; Manas, Derek M.
Abstract Introduction Patients with incidental pT2‐T3 gallbladder cancer (IGC) after a cholecystectomy may benefit from a radical re‐resection although their optimal treatment strategy is not well defined. In this Unit, such patients undergo delayed staging at 3 months after a cholecystectomy to assess the evidence of a residual tumour, extra hepatic spread and the biological behaviour of the tumour. The aim of this study was to evaluate the outcome of patients who had delayed staging at 3 months after a cholecystectomy. Methods From July 2003 to July 2011, 56 patients with T2‐T3 gallbladder cancer were referred to this Unit of which 49 were diagnosed incidentally on histology after a cholecystectomy. All 49 patients underwent delayed pre‐operative staging using multi‐detector computed tomography (MDCT) followed selectively by laparoscopy at 3 months after a cholecystectomy. Data were collected from a prospectively held database. The peri‐operative and long‐term outcomes of patients were analysed. SPSS software was used for statistical analysis. Results There were 38 pT2 and 11 pT3 tumours. After delayed staging, 24/49 (49%) patients underwent a radical resection, 24/49 (49%) were found to be inoperable on pre‐operative assessment and 1/49 (2%) patient underwent an exploratory laparotomy and were found to be unresectable. The overall median survival from referral was 20.7 months (54.8 months for the group who had a radical re‐resection versus 9.7 months for the group who had unresectable disease, P < 0.001). These results compare favourably with the reported outcome of fast‐track management for incidental pT2‐T3 gallbladder cancer from other major series in the literature. Conclusion Delayed staging in patients with incidental T2‐T3 gallbladder cancer after a cholecystectomy is a useful strategy to select patients who will benefit from a resection and avoid unnecessary major surgery.